Pengaruh Penggunaan Media Sandpaper Tray Terhadap Kemampuan Mengenal Bentuk Bangun Datar Geometri Anak Usia 4-5 Tahun - Liwaurrohmah, Suci; Isnaningsih, Anti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research was conducted on children aged 4-5 years at RA Tuhfatul Athfal which was motivated by the fact that children's cognitive development in recognizing geometric shapes was still not optimal, this was because teachers had not optimally utilized the use of sandpaper tray media to develop children's cognitive abilities. This research method is quantitative. The design type of this research is Quasi Experiment with a one-group pretest-posttest design. The subjects in this research were 20 children aged 4-5 years. The data analysis technique in this research used t-test techniques and calculations. via SPSS. The statistical test in this study was to test whether the sandpaper tray media had an effect on the ability to recognize flat geometric shapes in children aged 4-5 years at RA Tuhfatul Athfal. Then from the results of the t test calculations, Sig (0.000) < 0.05 was obtained. So the conclusion of this research is that there is an influence of sandpaper tray media on the ability to recognize flat geometric shapes in children aged 4-5 years in Ra Tuhfatul Athfal